Systemic Inflammation Index Values Are Associated With Worsened Disease Severity and Poor Response to Autoimmune Encephalitis Treatment - Mei, Yanliang; Yang, Jing; Yuan, Yanpeng; Liu, Yutao; Liu, Xiaojing; Li, Mingli; Fan, Shiheng; Li, Lanjun; Jiang, Chenyang; Xu, Yuming (Frontiers in Neurology, 2021)
Both specific and innate immune responses play important roles in autoimmune encephalitis (AE). We aimed to explore the predictive value of the systemic inflammation index (SII) at admission as a peripheral biomarker of treatment response of AE. A total of 146 patients diagnosed with AE in the First Affiliated Hospital of Zhengzhou University from January 1, 2018 to September 22, 2020 were retrospectively and consecutively analyzed as per the inclusion criteria and divided into two groups according to their response to immunotherapy after 30 days. The predictive value of the SII as a peripheral biomarker for AE treatment response was calculated using the receiver operating characteristic curve analysis, which showed that the best SII cut-off value for predicting poor response to AE treatment was 863.3; the area under the curve was 0.75, with 83.0% sensitivity and 72.0% specificity. The risk factors for poor response to AE treatment were analyzed; univariable analysis showed that the rate of decreased level of consciousness, rate of cognitive or mental behavior abnormality, cerebrospinal fluid pressure, blood neutrophils, platelets, time until treatment initiation, neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, and SII were significantly higher in patients with poor response to AE immunotherapy after 30 days than in patients with good response. Meanwhile, the blood lymphocyte counts and Glasgow Coma Scale (GCS) scores in patients with poor response were significantly lower than those in patients with good response (all p<0.05), and multivariable binary logistic regression with backward stepwise method showed that decreased levels of consciousness, time until treatment initiation and SII were associated with poor response to immunotherapy. Moreover, the SII ≤ 863.3 group had lower rates of decreased consciousness levels, admission to the intensive care unit, and mechanical ventilation; lower cerebrospinal fluid pressure, blood neutrophil count, and platelet count; and higher blood lymphocyte count and GCS scores. The SII was associated with worsened disease severity and poor response to treatment after 30 days of the initially diagnosed AE, and patients with an SII > 863.3 were more likely to have poor response to immunotherapy.